Detailed information mitigates confidence inflation - Iida, Ryosuke (Psychology, crime & law, 2021)
Jurors distrust eyewitness testimony when eyewitness confidence is inflated between the incident and identification in court. Nevertheless, jurors may view inflated-confidence testimony as reliable if the eyewitness gives a justification for the inflation. Researchers have not examined how this ‘recovery of eyewitness credibility’ is affected by specific features of the justification (i.e. degree of detail). In Experiment 1, we manipulated the degree of detail in post-confidence-inflation eyewitness justifications containing information related to a witnessed criminal. We examined the effects of such justifications on participants’ ratings of the eyewitness testimony. Although highly detailed but inconsistent eyewitnesses who gave a related justification were not able to fully recover their credibility, we found that they showed reduced credibility loss relative to eyewitnesses who gave a less detailed justification or no justification. In a second experiment, we investigated the possibility that an eyewitness with inflated confidence could recover their credibility with a justification containing information unrelated to the criminal. Interestingly, we found that even when the justification was unrelated to the criminal, highly detailed but inconsistent eyewitnesses could mitigate some of their credibility loss. Implications for the mechanisms underlying eyewitness credibility recovery, and their ramifications for real-world cases are discussed.